2021
DOI: 10.2807/1560-7917.es.2021.26.5.2100092
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to SARS-CoV-2 protect against re-infection during outbreaks in care homes, September and October 2020

Abstract: Two London care homes experienced a second COVID-19 outbreak, with 29/209 (13.9%) SARS-CoV-2 RT-PCR-positive cases (16/103 residents, 13/106 staff). In those with prior SARS-CoV-2 exposure, 1/88 (1.1%) individuals (antibody positive: 87; RT-PCR-positive: 1) became PCR-positive compared with 22/73 (30.1%) with confirmed seronegative status. After four months protection offered by prior infection against re-infection was 96.2% (95% confidence interval (CI): 72.7–99.5%) using risk ratios from comparison of propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 9 publications
(12 reference statements)
4
61
1
Order By: Relevance
“…Although we did not observe reinfection episodes in our cohort, others have reported reinfection episodes. A 96% protective effectiveness in prior infected patients was estimated in care homes outbreaks [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not observe reinfection episodes in our cohort, others have reported reinfection episodes. A 96% protective effectiveness in prior infected patients was estimated in care homes outbreaks [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with a similar demographic and setting are thus far limited. One study of subsequent outbreaks in two nursing homes in the United Kingdom found that 1.1% of residents were found to have repeat positive PCR tests over the two outbreaks [14] . In the United States, a study of two outbreaks in a Kentucky nursing home separated by three months found that five residents had probable reinfections, and that severity was worse in all residents, with one death reported [15] .…”
Section: Discussionmentioning
confidence: 99%
“…The present study shows that NH residents with prior COVID-19 achieve much higher S-protein IgG levels after one single jab than in younger COVID-19 convalescents 35 . It remains to be determined whether vaccinated residents with prior COVID-19 (with at least one jab) will be better protected against reinfection during outbreaks in NHs than unvaccinated residents with prior COVID-19 4 .…”
Section: Findings Of the Present Study In Light Of Current Publications On Residents With Prior Covid-19mentioning
confidence: 99%
“…In NHs facing a COVID-19 outbreak, infection prevention and control (IPC) measures based on results of repeated testing by real-time reverse-transcriptase polymerase chain reaction for SARS-CoV-2 (RT-PCR) in all residents can limit coronavirus transmission 2,3 . Residents with a prior COVID-19 may be protected against reinfection during outbreaks in NHs 4 .…”
Section: Introductionmentioning
confidence: 99%